2020
DOI: 10.1017/jfm.2020.584
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Richtmyer–Meshkov instability of heavy gas layer with perturbed inner surface

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Recently, shock-induced inclined SF 6 curtain evolution was explored (Olmstead et al 2017;Romero et al 2021), and it was found that the pressure waves inside the heavy gas are responsible for the scale selection in fully three-dimensional initial conditions, resulting in the Kelvin-Helmholtz instability (KHI) becoming dominant. The soap-film technique was recently utilised to study the interaction of a converging shock wave and a heavy or light fluid layer (Ding et al 2019;Li et al 2020;Sun et al 2020). Compared with the planar RMI, the additional geometric convergent effect (Bell 1951;Plesset 1954) and Rayleigh-Taylor stabilisation (RTS) effect induced by high pressures near the focusing point (Luo et al 2018), introduced by the cylindrical or spherical RMI, complicate the analysis on the fluid-layer evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, shock-induced inclined SF 6 curtain evolution was explored (Olmstead et al 2017;Romero et al 2021), and it was found that the pressure waves inside the heavy gas are responsible for the scale selection in fully three-dimensional initial conditions, resulting in the Kelvin-Helmholtz instability (KHI) becoming dominant. The soap-film technique was recently utilised to study the interaction of a converging shock wave and a heavy or light fluid layer (Ding et al 2019;Li et al 2020;Sun et al 2020). Compared with the planar RMI, the additional geometric convergent effect (Bell 1951;Plesset 1954) and Rayleigh-Taylor stabilisation (RTS) effect induced by high pressures near the focusing point (Luo et al 2018), introduced by the cylindrical or spherical RMI, complicate the analysis on the fluid-layer evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In the spherical mixing layer, the turbulent mixing exhibited stronger anisotropy at large scales than that at small scales and the inertial sub-region of kinetic energy and density spectra also showed a Kolmogorov-like −5/3 scaling law in late time, which indicated that the turbulent scales were rarely affected by the spherical mixing layer curvature. By numerically simulating two-dimensional single-mode interfaces driven by convergent shock waves, Tang et al (2021) investigated the effects of the Atwood number on the compressibility, RT stabilization and the nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations of cylindrical converging RMI in shock tubes had been conducted by several researchers, such as Hosseini & Takayama (2005), Biamino et al (2015), Luo et al (2015Luo et al ( , 2018Luo et al ( , 2019a, Zhai et al (2017), Rodriguez et al (2017), Ding et al (2017Ding et al ( , 2019, Lei et al (2017), Li et al (2020), Vandenboomgaerde et al (2018, Courtiaud et al (2019), Sun et al (2020b) and Zou et al (2019). These experimental results are particularly helpful for the development of theory and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the soap film technique was recently utilised to generate an SF 6 gas layer with controlled perturbation and layer thickness. The heavy-fluid-layer evolution induced by a planar shock wave (Liang et al 2020;Liang & Luo 2021a,b) or a cylindrical converging shock wave (Ding et al 2019;Sun et al 2020) was explored. It was found that rarefaction waves and compression waves reverberating inside the heavy-fluid layer result in the first interface being more unstable and the second interface being more stable (Liang & Luo 2021a).…”
Section: Introductionmentioning
confidence: 99%